2003
DOI: 10.1002/bem.10130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 50 Hz electromagnetic field exposure on apoptosis and differentiation in a neuroblastoma cell line

Abstract: Experiments were carried out to assess whether a magnetic field of 50 Hz and 1 mT can influence apoptosis and proliferation in the human neuroblastoma cell line LAN-5. TUNEL assays and poly-ADP ribose polymerase (PARP) expression analysis were performed to test apoptosis induction, and the WST-1 assay was used to calculate the proliferation index in a long term exposure. No alterations were found in cellular ability to undergo programmed cell death, but a small increase in the proliferation index was evidenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 29 publications
6
40
1
3
Order By: Relevance
“…Pirozzoli et al (2003) finding confirmed our results. They have not found alterations in the cellular ability to undergo programmed cell death, after exposure of the neuroblastoma cell line to 50 Hz electromagnetic field (Pirozzoli et al 2003).…”
Section: Dapi Staining Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Pirozzoli et al (2003) finding confirmed our results. They have not found alterations in the cellular ability to undergo programmed cell death, after exposure of the neuroblastoma cell line to 50 Hz electromagnetic field (Pirozzoli et al 2003).…”
Section: Dapi Staining Resultssupporting
confidence: 93%
“…Other researches also confirmed that EL-EMF cannot promote caspase activation and cannot trigger the apoptosis pathway (Akdag et al 2010) (Jiménez-García et al 2010). Pirozzoli et al (2003) finding confirmed our results. They have not found alterations in the cellular ability to undergo programmed cell death, after exposure of the neuroblastoma cell line to 50 Hz electromagnetic field (Pirozzoli et al 2003).…”
Section: Dapi Staining Resultssupporting
confidence: 88%
“…Regarding differentiation under combined treatment, antagonistic interactions between ELF MF and differentiation promoters like NGF, MEL or retinoids, have been reported in different cell types [12,40,83,84]. The present results also show that the MF antagonizes the effects on AFP expression and ALB release, exerted by the assayed doses of MEL.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andsupporting
confidence: 66%
“…These parameters include the field strength, the wave form, the exposure cycle and duration, the genetic characteristics of the cells (66), the presence of pharmacological drugs or endogenous hormones like melatonin (19,67) or the redox status of the system (68). Pirozzoli et al (69) reported a significant increase (10%; p≤0.05) in proliferation of the human neuroblastoma cell line LAN-5, after 7 days of continuous exposure to 50 Hz, 1 mT MF. In our experiments a much shorter (2 days) intermittent exposure to a weaker (0.1 mT) MF induced a similar increase in proliferation (15%, p≤0.001) in other neuroblastoma line.…”
Section: Discussionmentioning
confidence: 99%